Preliminary remarks on Pascal's Écrits sur la grâce. (December 2013) - Parish, Richard
<x content-type="archive" xml:space="preserve">Abstract</x> The volume's first introductory essay shows how the Écrits sur la grâce throw up many challenges and puzzles for the reader, while still revolving around a core set of problems and definitions. The first is the attempt to situate Augustinian teaching on grace in the middle (and by implication orthodox) ground between Calvinism and (neo-)Pelagianism, in a way which appeals both to authority and to common sense; the second is to underline the double nature both of finding and of losing grace in a range of co-operative sequences. Finally there are the linked imperatives of ignorance and incuriosity, allowing Pascal to conclude only that the gift of grace or its lack is due to 'un jugement juste quoique caché', without which mystery the hubristic risk of antinomianism becomes all too apparent.